2018
DOI: 10.1186/s13756-018-0390-5
|View full text |Cite
|
Sign up to set email alerts
|

Germs of thrones - spontaneous decolonization of Carbapenem-Resistant Enterobacteriaceae (CRE) and Vancomycin-Resistant Enterococci (VRE) in Western Europe: is this myth or reality?

Abstract: BackgroundIn France, Carbapenem-Resistant Enterobacteriaceae (CRE) and Vancomycin-Resistant Enterococci (VRE) are considered as Extensively Drug-Resistant (XDR) bacteria. Their management requires reinforcement of hospital’s hygiene policies, and currently there is few consistent data concerning the spontaneous decolonization in XDR colonized patients. Our aim is to study the natural history of decolonization of XDR carriers over time in a hospital setting in a low prevalence country.Material and methodsRetros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 25 publications
1
18
0
1
Order By: Relevance
“…Spontaneous clearance of MDRO without treatment is not uncommon [57,65]. In a previous study, spontaneous eradication of VRE and CRE occurred in 48.2% of cases with a median time of 49 days [57]. On some occasions, spontaneous eradication of MDRO, rather than FMT, might have had a greater impact on the MDRO decolonization.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Spontaneous clearance of MDRO without treatment is not uncommon [57,65]. In a previous study, spontaneous eradication of VRE and CRE occurred in 48.2% of cases with a median time of 49 days [57]. On some occasions, spontaneous eradication of MDRO, rather than FMT, might have had a greater impact on the MDRO decolonization.…”
Section: Discussionmentioning
confidence: 90%
“…Most previous studies also showed no difference in the efficacy of FMT for eradication between gram-positive and gram-negative bacteria, and found no evidence for the possibility of any difference. A few studies have also shown similar median duration of spontaneous colonization of 45 to 306 days for VRE and 42 to 387 for CRE, although the results varied widely [52][53][54][55][56][57]. A recently published randomized controlled trial also showed that 29% (5/ 17) of patients in the control group without intervention had no MDRO colonization at the last followup [44].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous data regarding the duration of CPE carriage described mainly KPC CPE cases [ 18 , 23 , 24 , 25 , 26 ]. However, little is known about the duration of carriage of OXA-48-like CPE and NDM CPE [ 27 , 28 , 29 ]. To the best of our knowledge, this is the first study to evaluate the clinical risk factors of prolonged carriage of OXA-48-like CPE with the largest number of cases ( n = 116).…”
Section: Discussionmentioning
confidence: 99%